Cross‐Linked Double Network Graphene Oxide/Polymer Composites for Efficient Coagulation‐Flocculation. Issue 1 (1st October 2019) - Lin, Shuyuan; Li, Qilong; Zhong, Yujia; Li, Jing; Zhao, Xuanliang; Wang, Min; Zhao, Guoke; Pan, Jialiang; Zhu, Hongwei
Abstract: Hybrid coagulant/flocculant consisting of nanomaterials have tremendous potential in solid‐liquid separation and can be applied to the coagulation‐flocculation‐sedimentation process of water treatment. In this work, inspired by the mineralization in nature, a graphene oxide/polymer‐based hybrid coagulant/flocculant that precipitates large‐scale, multicomponent (e.g., dyes, heavy metal ions, and nanoparticles) and complex pollutants simultaneously at room temperature by forming double‐network hydrogel through bioinspired Ca 2+ crosslinking, is developed for the purification of wastewater. The coagulation‐flocculation‐sedimentation method developed here also provides a novel strategy for the preparation of macroscopic assemblies of multicomponents that can be applied to various application fields. Abstract : This work demonstrates a graphene oxide/polymer‐based hybrid coagulant/flocculant, precipitating large‐scale, multicomponent (e.g., dyes, heavy metal ions, and nanoparticles) and complex pollutants simultaneously at room temperature by forming a double‐network hydrogel through Ca 2+ crosslinking to achieve the purification of wastewater. This method also provides a novel strategy for the preparation of macroscopic assemblies of multicomponents that can be applied to various application fields.